(untitled) (PERcursos Linguísticos, 2025)
This article examines literary scenography, focusing on the enunciation in which the voice of a son and the spatiotemporal coordinates within a discursive event of fatherhood, affiliation, and mourning structure the literary discourse in O peru de Natal by Mário de Andrade. We draw on the French tradition of Discourse Analysis (DA), particularly its enunciative-discursive perspective, emphasizing Maingueneau’s hypothesis of literary discourse, which views literature as a linguistic dimension of the text. Literary discourse fits within the framework of its constituents and assumes properties relative to its conditions of emergence, functioning, and circulation. Our hypothesis is that literary scenography, society, and traditions shape Mário de Andrade’s subjectivity and integrate the socio-historical conditions of discourse production. Our findings confirm scenography as both a condition and product of discourse, involving a paratopic process that legitimizes this type of discourse. Moreover, O peru de Natal, through its developments, engages with the literary movement, validates the expression of a son’s suffering and misfortunes as he attempts to overcome familial and personal mourning during a Christmas gathering. Mário de Andrade, as the agent of the creative process, finds no other means of linguistic-literary investment but discursive production.